Studi Optimal Power Flow pada Sistem Kelistrikan 500 kV Jawa-Bali dengan Menggunakan Particle Swarm Optimization (PSO) - Taqiyuddin; Sasongko Pramono Hadi (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
This paper presents a Particle Swarm Optimization (PSO) method to solve Optimal Power Flow (OPF) problem. The proposed PSO method is used to minimize power losses in transmission line with involves two stages optimization, namely the minimization of power generation and followed by the minimization of reactive power or Optimal Reactive Power Dispatch (ORPD) in the optimization process. Then, this approach is applied to the 500 kV Java-Bali electrical power system during peak loads. Simulation results on the 500 kV Java-Bali electrical power system showed that, the proposed method is able to reduce power losses in transmission lines and also production costs amounted to 23.37 MW or 17.85% and amounted to RP 631.61 million per hour or 9.63%, respectively, compared with PT. PLN (Persero) operational data.